(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
In the following analysis, we tried first to contextualize La loa El Divino Narciso from Sor Juana Inés de la Cruz within esthetical and cultural paradigms of her time. Then, we tried to update her critical reading from the perspective of a subordinate rhetoric or poetics. We understand it as the literary deconstruction and subsequent reorganization of the meanings that justified colonialism. This approach has the purpose of accounting for the way in which accurate manipulation of hegemonic codes makes it possible to reverse the symbolic contents of one of the earliest and most persistent representations of the American continent: the America-woman figure. This image naturalized and justified its otherness.